Plant-based remedies for wolf bites and rituals against wolves in the Iberian Peninsula: Therapeutic opportunities and cultural values for the conservation of biocultural diversity. (14th September 2017) - González, José A.; Carvalho, Ana Maria; Vallejo, José Ramón; Amich, Francisco
Abstract: Ethnopharmacological relevance: Combined approaches to local knowledge and folk plant use improve awareness and promote effective strategies for the conservation of significant biocultural patrimony. Moreover, the information reported might be the basis for further appropriate phytochemical and pharmacological research. Therefore we provide an insight into traditional herbal remedies and practices for healing bite injuries in humans and domestic animals caused by the Iberian wolf. Wolf bites are associated with inflammatory processes and rabies is a potential complication Aims: This paper describes and summarises the medicinal-veterinary empirical and ritual uses of the Iberian flora for wolf injuries and reviews the ethnopharmacological data of specific plants that are already published. The Iberian wolf is a critically endangered subspecies of the grey wolf. Livestock attacks attributed to wolves are increasingly frequent in the Iberian Peninsula, resulting in serious social problems. Interesting strategies for Iberian wolf conservation might be related to traditional grazing practices that are deeply linked with empirical knowledge and local practices passed on by oral tradition, which are also vulnerable now. Materials and methods: Based on documentary sources from the beginning of the twentieth century to the present, we systematically searched old monographs, regional documents, technical papers, project reports, as well as the international and national databases and the available scientific literature, without restrictions regarding the language of the publications consulted. Results: A total of 39 remedies for healing wolf bite injuries in humans and domestic animals was reported, highlighting the medicinal use of 33 species of vascular plants, mostly wild herbs, belonging to 18 botanical families. The use of wood ashes was also reported. The number of use-reports found represents a very high number considering similar European studies. Leaves were the predominant plant part mentioned. Boiling plant materials in water for topical uses was the most frequent method of preparation found. Some traditional remedies combined two or more plant species in order to potentiate their effects. Moreover, some plant-based traditional practices and rituals to ward off wolves and to prevent wolf attacks were also documented. In these practices eleven other species (belonging to seven more families) were used. Conclusions: Despite the decline of the Iberian wolf over the last few decades, wolves are still in the imaginary of rural communities that perceive this large carnivore as both a diabolic creature and a mythic and benign animal. Wolf-related cultural heritage is of great interest in terms of conservation strategies. This review emphasises the importance of local knowledge and provides useful information about several potential sources of phytochemicals and their claimed therapeutic effects, aiming at contributing to the conservation and appreciation of the Iberian biocultural heritage. Graphical abstract: